Two divergent immune receptors of the allopolyploid Nicotiana benthamiana reinforce the recognition of a fungal microbe-associated molecular pattern VdEIX3 - Wang, Nan; Yin, Zhiyuan; Zhao, Yaning; Li, Zhengpeng; Dou, Daolong; Wei, Lihui (Frontiers in Plant Science, 2022)
The allotetraploid Solanaceae plant Nicotiana benthamiana contains two closely related receptor-like proteins (RLPs), NbEIX2 and NbRXEG1, which regulate the recognition of VdEIX3 and PsXEG1 respectively. VdEIX3, PsXEG1, and their homologs represent two types of microbe-associated molecular patterns (MAMPs) that are widespread in diverse pathogens. Here, we report that NbRXEG1 also participates in VdEIX3 recognition. Both nbeix2 and nbrxeg1 single mutants exhibited significantly impaired but not abolished ability to mediate VdEIX3-triggered immune responses, which are nearly abolished in nbeix2 nbrxeg1 double mutants. Moreover, a dominant negative mutant of nbeix2 that contains a 60 bp deletion failed to respond to VdEIX3 and could suppress VdEIX3-induced cell death in the wild-type N. benthamiana. Further phylogenetic analyses showed that NbEIX2 and NbRXEG1 are obtained from different diploid ancestors by hybridization. These results demonstrate that the allotetraploid N. benthamiana recognizes two types of MAMPs by two homologous but diverged RLPs, which provides a model in which an allopolyploid plant probably exhibits defense hybrid vigor by acquiring divergent immune receptors from different ancestors.